METODE TAFSIR MAWá¸ŒÅªâ€™Äª: Studi Komparatif antara Muhammad Al-GhazÄlÄ« dan - Nailil Muna (STAI AL-ANWAR SARANG, 2018)
This article analyzes the mawḍū'ī method of interpretation. This study aims to identify and explain the differences in the mawḍū'ī interpretation method between Muhammad al-Ghazālī and Abd al-Ḥayy al-Farmāwī. Seeing from the significant differences in operationalizing the mawḍū'ī method of interpretation, in which Muhammad al-Ghazālī interprets the verses of the al-Qurʻan departing from the text then sees reality while Abd al-Ḥayy al-Farmāwī interprets the verses of the al-Qurʻan departing from reality then sees the text. Through the analysis of the history of the idea of ​​the Quranic interpretation of Ignaz Goldziher, this study shows that the concept of the mawḍū'ī method offered by Muhammad al-Ghazālī and Abd al-Ḥayy al-Farmāwī is very different. The concept offered by al-Ghazālī is interpreting al-Qur ʻan according to the order of the surah or tartīb 'uthmāni which contains a theme and is related between one part of the chapter and another, so that the face of the surah seems like a perfect and complementary form. Meanwhile al-Farmāwī interprets al-Qur ʻan by compiling all the verses on the same theme, putting them under one title then interpreted by the mawḍū'ī method. The implication of the mawḍū'ī method offered by Muhammad al-Ghazālī for the final result of interpretation is the birth of a comprehensive-systematic work, while the implication of the mawḍū'ī method offered by Abd al-Ḥayy al-Farmāwī for the final result of interpretation is the birth a work of applicative-realistic interpretation.